Bioclimatic characterization of the Subtropical Mountain Forests of Yungas at the northern extreme of Argentina: Sierras de Tartagal, Alto Macueta and Alto del Rio Seco (Salta Province) - Villalba, Maria Soledad; Entrocassi , Gabriela; Martínez Carretero , Eduardo (Mediterranean Botany, 2024)
The Subtropical Mountain Forests of Yungas at the northern extreme of Argentina (Sierras de Tartagal, Alto Macueta and del Alto Río Seco, Salta Province) were bioclimatically characterized for the first time. In this study, the methodology of the Bioclimatic Classification of Earth was applied. Twelve Temperature and Precipitation climatic parameters were used and three bioclimatic indices corresponding to 54 Bioclimatic Reference Localities (BRL) established in the study area were also calculated. From them we determined the bioclimatic units of each BRL at the level of Macrobioclimate, Bioclimate, Thermotypes and Ombrotypes. Subsequently, three bioclimatic maps (Bioclimate, Thermotypes and Ombrotypes) and two bioclimatic distribution maps of the forests and its vegetation belt (Premontane Forest and Montane Rainforest) were digitally developed using the QGIS software. The results obtained show that these forests are distributed within the Tropical Macrobioclimate and Tropical Pluviseasonal Bioclimate, with Upper Thermotropical and Lower Mesotropical thermotypes and Lower Subhumid and Upper Subhumid ombrotypes. The lowest vegetation belt, the Premontane Forest, is distributed between (≈400) 429‒889 (≈900) m asl and exhibits two thermal variants: the warm Thermotropical Premontane Forest and the more temperate Mesotropical Premontane Forest. The Montane Rainforest is distributed at higher altitudes between (≈900) 965‒1178 (≈1200) m asl under Lower Mesotropical Thermotype. Both vegetation belts present two ombric variants, whose geographic distribution is determined by the precipitation gradient operating in the region: towards the West, the more humid variants are distributed under the Upper Subhumid ombrotype, while towards the East, the less humid variants are found under Lower Subhumid ombrotype. The present work constitutes the first bioclimatic study carried out in this forest formation applying the methodology of the Bioclimatic Classification of the Earth. It also lays the foundations and contributes whith valuable information to future floristic, vegetational, ecological and biogeographical studies and those focused on the conservation and sustainable management of native forests at the northern extreme of Argentina.